Evaluation of load–deformation behavior of reinforced concrete shear walls with continuous or lap-spliced bars in plastic hinge zone. Issue 3 (February 2019) - Zhi, Qing; Zhou, Binbin; Zhu, Zhangfeng; Guo, Zhengxing
This article presents an analysis procedure for evaluation of load–deformation behavior of reinforced concrete shear walls with continuous or lap-spliced bar connections in plastic hinge zones under horizontal loads. For the shear walls with continuous bars, the lateral deformations caused by flexure, shear, and reinforcement slip are evaluated by considering their interaction. The flexural deformation is calculated by conventional fiber model. The shear mechanism is based on modified compression field theory with a softened smeared cracked reinforced concrete membrane element. Both the flexural and shear deformations are estimated separately in the plastic hinge and non-plastic hinge regions. In addition, an approach is proposed for analysis of plastic hinge length based on fracture energies of materials. For the shear walls with lap-spliced bars, due to its complicated behavior and mechanism, a simple way to deal with the lap splice is proposed. The equations regarding bond-slip of the lap splice with minimum spliced length are established and the stress and strain states of lap splices with different spliced lengths are analyzed on the basis of equilibrium of forces with a mean bond stress model. Finally, the validity of the proposed analysis procedure is confirmed by comparing the analytical results with previous experimental data.